STUDI KASUS DAN PRAKTIK MANAJEMEN PENDIDIKAN ISLAM DALAM PENINGKATAN MUTU LEMBAGA PENDIDIKAN - Yosef Maulana; Yuliani Syam; Mustakim; Asep Awaludin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to analyze the concepts, case studies, and practices of Islamic education management in improving the quality of educational institutions. The method used is a qualitative approach with library research. The results of the study indicate that Islamic education management is a process of managing educational institutions that integrates modern management functions with Islamic values ​​such as trustworthiness, justice, and responsibility. The case studies indicate that the main problems lie in weak planning, limited human resources, and a suboptimal evaluation system. Effective management practices include strategic planning, competency-based organization, innovative learning implementation, and ongoing supervision. With the implementation of good management, Islamic educational institutions can improve the quality of education and shape the character of students who excel intellectually and spiritually.